The Development of Webbed Integrated Science Module Based on Local Wisdom with Pupuik Sarunai Theme - Kurniawati, Sri; Evita Putri, Rahmah; Yurnetti; Nuzullah Putri, Azza (SEMESTA: Journal of Science Education and Teaching, 2025)
The learning objectives more effectively by using science teaching materials. These materials become more insightful when they incorporate and build upon local wisdom. One way to integrate science is by using a webbed model. Therefore, this study aims to produce a valid and practical webbed type Integrated Science module based on local wisdom with the Pupuik Sarunai theme. This type of research was Research and Development (R&D). This research used the ADDIE development model which had stages of analysis, design, development, implementation and evaluation. However, due to the limited time and cost of research only conducted up to the stage of development (development) and for implementation and evaluation was not conducted yet. This study used an instrument consisting of a validity test and a practicality questionnaire. The data obtained from the results of the study were calculated using Moment Kappa (k) to analyze the results of the validity and practicality tests of the Integrated Science module. The results of the research that has been done indicate that the practicum module developed has a validity test result of 0.87 with a very valid category. The results of the practicality test of the practicum module by the teacher were very practical with the results of 0.87 and the results of the student practicality test were included in the practical category with the results of 0.77. Therefore, it can be concluded that the webbed type Integrated Science module based on local wisdom with the Pupuik Sarunai theme is valid and practical.